AFFIRMATIVE ACTION DI ERA REFORMASI DAN IMPLIKASINYA TERHADAP PEMBANGUNAN BERWAWASAN GENDER - Silvia Hanani (Universitas Islam Negeri Imam Bonjol Padang, 2012)
The low participation and involvement of women in politics has seen some discrimination and injustice against women, because they do not attention development policies are gender oriented. It is well recognized by women in Indonesia, so the post-New Order government women's advocacy movement that gave birth to affirmative action that essentially encourages and guarantees against women to be involved in politics. Significant impact of affirmative action is the birth of a minimal system of representation of women in parliament 30%. This representation system, reinforced in 2009 with the implementation zipper election system, where from 1-3 candidates proposed must be female. But somehow affirmative action, can not be denied as a form be balanced with minimizing the lack of women and men. Keywords : Affirmative action, politics and participation of womenCopyright © 2012 by Kafa`ah All right reservedDOI : 10.15548/jk.v2i1.45